Salivary glands in workers of Ruptitermes spp. (Blattaria, Isoptera, Termitidae, Apicotermitinae): a morphological and preoteomic approach - Costa-Leonardo, Ana Maria [UNESP]; da Silva, Iago Bueno [UNESP]; Janei, Vanelize [UNESP]; Poiani, Silvana Beani [UNESP]; dos Santos-Pinto, José Roberto Aparecido [UNESP]; Esteves, Franciele Grego [UNESP]; Palma, Mario Sérgio [UNESP] (Springer Nature, 2021)
Salivary glands are omnipresent in termites and occur in all developmental stages and castes. They function to produce, store, and secrete compounds, ranging from a feeding function to defensive mechanisms. Here, we provide a complete morphological overview of the salivary glands in the soldierless species Ruptitermes reconditus and R. xanthochiton, and the first proteomic profile of the salivary glands in a Neotropical Apicotermitinae representative, R. reconditus. Salivary glands from both species were composed of several acini, roughly spherical structures composed of two types of central cells (type I and II) and peripheral parietal cells, as well as transporting ducts and two salivary reservoirs. Central cells were richly supplied with electron-lucent secretory vesicles and rough endoplasmic reticulum, a feature of protein-secreting cells. Parietal cells of Ruptitermes spp. had conspicuous characteristics such as electron-lucent secretory vesicles surrounded by mitochondria and well-developed microvilli. Moreover, different individuals showed variation in the secretory cycle of salivary acini, which may be related to polyethism. Ultrastructural analysis evidenced a high synthesis of secretion and also the occurrence of lysosomes and autophagic structures in central cells. Proteomic analysis of the salivary glands revealed 483 proteins divided into functional groups, highlighting toxins/defensins and compounds related to alarm communication and colony asepsis. Soldierless termites are quite successful, especially due to morphological adaptations of the workers, including unknown modifications of exocrine glands. Thus, according to our morphological and proteomic findings, we discuss the potential roles of the salivary gland secretion in different social aspects of the sampled species.
Keywords: Central cells; LCMS-based proteomics; Parietal cells; Secretion; Toxin-like proteins